Impak Kerja Giliran ke atas Emosi, Fizikal dan Mental dalam kalangan Pegawai Penjara - Subramaniam, Adinaraina; Mustaffa, Jamaludin; Ab Hamid, Kamal; Hamzah, Mohd Hilmi (UUM Press, 2016)
This study aimed to investigate the effect of shift work on the emotional, physical and mental health among prison officers in Pokok Sena Prison, Kedah. These prison officers are employees who worked the morning, afternoon and night shifts on a fixed rotation. In addition, this study is also carried out to identify the level of influence of the angle of rotation of emotional, physical and the mental faced prison officer who had worked shifts for dismantling concoction of this study. The instrument used in this study is through a survey where questionnaires were given out to obtain information that contains items that can measure the aspects of emotional, physical, mental and psychological as required by the variables. The retrieved data were analyzed using descriptive statistics and statistical inference (t-test). Other than that, the data were analyzed using the Statistical Packages for Social Sciences (SPSS) version 16.0 software. A total of 300 prison officials at Pokok Sena Prison were selected as the subject study. The implication of the study showed that the schedule of shift work has an impact on the physical medium, but there is a higher impact on the emotional and mental prison officers based on their experience. The study also showed there was a significant shift work among prison officers compared officers working the non-shift rotation. All of the above findings carry implications that kind of work time practiced together some work and non-work factors can affect the emotions, mental and physical state of the prison officers.